The scope of state’s responsibility to limit climate change - Pommere, Zane (Riga Graduate School of Law, 2020)
The work is structured in three main sections – first covers the theoretical grounds on defining what is climate change and all the main international agreements that regulates climate change and that many states have joined in order to limit climate change and reduce the negative impacts it brings. The second part consists of the analysis of the supranational and national level of climate initiatives and possible challenges during their introduction and transposition process into national laws. Lastly, the work concludes with the third part that is devoted to the implementation aspects of state responsibility towards climate change.The purpose of this work is to examine the scope of the responsibility that lies upon states to limit climate change and the international responsibilities they have undertaken in order to achieve it. Throughout the work, the author has tried, through analyzing the international agreements regulating climate change, the commitments states have themselves undertaken in order to fulfil climate goals and through best practice on implementing different climate initiatives, to find the best possible solutions on how to implement these international commitments in national law.
Keywords: Research Subject Categories::LAW/JURISPRUDENCE::Other law::International law; Research Subject Categories::LAW/JURISPRUDENCE::Other law::Environmental law; Climate change